Cardiopulmonary resuscitation coaching for resuscitation teams: A systematic review - Kasper G. Lauridsen; Emma Bürgstein; Sabine Nabecker; Yiqun Lin; Aaron Donoghue; Jonathan P. Duff; Adam Cheng (Resuscitation Plus)
Aim: Cardiopulmonary resuscitation (CPR) quality is often substandard to guidelines for resuscitation teams. We aimed to investigate if the use of a CPR coach as part of the resuscitation team can improve teamwork, quality of care, and patient outcomes during simulated and clinical cardiac arrest resuscitation. Methods: We searched PubMed, Embase, and Cochrane from inception until October 9, 2024 for randomized trials and observational studies. We assessed risk of bias using Cochrane tools and assessed the certainty of evidence using the Grading of Recommendations Assessment, Development and Evaluation approach. PROSPERO CRD42024603212. Results: We screened 505 records and included 7 studies. Overall, 6 were randomized studies involving pediatric resuscitation of which 4 studies were secondary analyses of one simulation-based trial, and one was an observational study on adult out-of-hospital cardiac arrest. Reported outcomes were: CPR performance in a simulated setting (n = 3), workload in a simulated setting (n = 2), adherence to guidelines in a simulated setting (n = 1), team communication in a simulated setting (n = 1), and clinical CPR performance (n = 1). All studies suggested improved CPR quality and guideline adherence when using a CPR coach compared to not using a coach. Risk of bias varied from low to critical and the certainty of evidence across outcomes was low or very low. Conclusions: We identified low- to very-low certainty of evidence supporting the use of a CPR coach as part of the resuscitation team in order to improve CPR quality and guideline adherence. However, further research is needed, in particular for clinical performance and patient outcomes.